2004
DOI: 10.1002/ejic.200300351
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 1,2‐Bis[(2,6‐diisopropylphenyl)imino]acenaphthene (dpp‐bian) with Alkali Metals − A Study of the Solution Behaviour of (dpp‐bian)n[M+]n (M = Li, Na; n = 1−4) with UV/Vis, ESR and 1H NMR Spectroscopy

Abstract: An excess of lithium or sodium in diethyl ether consistently reduces 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene (dpp-bian) to the mono-, di-, tri-and tetraanion, (dppbian)The process of reduction is easily observed by the change in colour of the solution, on going from the neutral ligand (yellow) to the monoanion (red), the dianion (green for Na or Li in Et 2 O; dark blue, followed by green, for Li in TMEDA), the trianion (brown) and the tetraanion (red-brown). In each reduction the maximum of the absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 21 publications
6
42
0
6
Order By: Relevance
“…[10] On going from neutral dpp-bian to its mono-and further to its dianion, the molecular parameters of the dpp-bian skeleton change significantly with respect to the bond lengths within the diimine part as well as to the metal-nitrogen distances. The metal-metal bond lengths in 2 (2.3598(3) ) and 3 (2.3531 (8) ) are close to that in 1 (2.3321(2) ). The increasing population of the LUMO on going from neutral dpp-bian to its radical anion and further to the dianion must result in a shortening of the central C À C bond and simultaneously in an elongation of the C À N distances within the diimine moiety.…”
Section: Wwwchemeurjorgmentioning
confidence: 52%
See 2 more Smart Citations
“…[10] On going from neutral dpp-bian to its mono-and further to its dianion, the molecular parameters of the dpp-bian skeleton change significantly with respect to the bond lengths within the diimine part as well as to the metal-nitrogen distances. The metal-metal bond lengths in 2 (2.3598(3) ) and 3 (2.3531 (8) ) are close to that in 1 (2.3321(2) ). The increasing population of the LUMO on going from neutral dpp-bian to its radical anion and further to the dianion must result in a shortening of the central C À C bond and simultaneously in an elongation of the C À N distances within the diimine moiety.…”
Section: Wwwchemeurjorgmentioning
confidence: 52%
“…The solution ESR spectrum of 3 reveals the coupling of an unpaired electron with the gallium nuclei According to the results of the X-ray crystal structure analyses the metal-metal bond lengths in 2 (2.3598(3) ) and 3 (2.3531 (8) ) are close to that found in 1 (2.3321(2) ). The electronic structures of compounds 2 and 3 were studied by DFT (B3 LYP/ 6-31G* level).…”
Section: With K 3 a C H T U N G T R E N N U N G [Dpp-bian] And The Hementioning
confidence: 52%
See 1 more Smart Citation
“…Considering that imine proton couplings of about 5.5 G are normally observed for the aryl-substituted diazabutadiene ligands (Table 1), the observed 3.8 G coupling in 10 (with no imine protons) is significant and must be assigned to the ring protons (labelled H 1 in Scheme 1) of the naphthalene fragment. Recently Fedushkin et al, [22] reported the EPR spectra of the mono-and trianions of the same 1,2-bis{(2,6-diisopropylphenyl)imino}acenaphthene ligand (Ar-BIAN) in complexes with alkali metal cations. The dimeric sodium derivative of the monoanion (ie., [Na + (Ar-BIAN) À ] 2 ) produced resolved couplings to two nitrogen nuclei (4.6 G) and two sodium nuclei (1.7 G), indicating that the unpaired electron was mainly localised over the diimine part of the Ar-BIAN ligand.…”
mentioning
confidence: 99%
“…Reduction of dpp BIAN with metallic mag nesium or calcium in THF affords exclusively com plexes with the dpp BIAN dianion of composition (dpp BIAN) 2-M 2+ (thf) n (M = Mg, n = 3; M = Ca, n = 4). 3 We have also synthesized 4 two new ligands of this type, viz., 1,2 bis[(2,5 di tert butylphenyl)imino]ace naphthene (dtb BIAN) and 1,2 bis[(2 diphenyl)imi no]acenaphthene (dph BIAN), as well as their magne sium and calcium derivatives (dtb BIAN) 2-Mg 2+ (thf) 2 and (dph BIAN) 2-M 2+ L n (M = Mg, L = DME, n = 2; M = Ca, L = thf, n = 3).…”
mentioning
confidence: 99%